METODE DRILL TERHADAP KEMAMPUAN MENULIS PERMULAAN ANAK AUTIS DI SEKOLAH DASAR LUAR BIASA - FARID ILHAM, MOCHAMMAD (Jurnal Pendidikan Khusus, 2017)
ABSTRACT:Writing was a speech skill which was used to communicate indirectly. Writing was an activity which behaved productive and effective through a lot of training and practicing regularly. For autism children, beginning writing ability was required so much because beginning writing ability was the pre-requirement for the effort to learn various subject matters. This research purpose was to prove whether there was influence of drill method application toward beginning writing ability to autism children in SDLB Bandaran 3 Winongan Pasuruan or not. The research method used was quantitative with pre-experimental design arrangement and one group pretest – posttest design. The data was collected using test and documentation techniques. The technique of data analysis used was statistic non parametric with n = 6 and α = 5% and it was analyzed using Sign test formula. The research result indicated that the result of pretest average value was 57,99 and the result of posttest average value was 81,25 while the result of data analysis indicated that Zh value (2,05) and Z table 5% (1,96) so the interpretation was Zh > Zt. So, it could be concluded that Ha was accepted. It meant there was influence of drill method application toward beginning writing ability to autism children in SDLB Bandaran 3 Winongan Pasuruan.   Keywords: Drill method, beginning writing